Respuesta :
ok
solution is
(x,y)
so
add the equations together to cancel y''s
4x+y=2
x-y=3 +
5x+0y=5
5x=5
divide 5
x=1
subsitute
4x+y=2
4(1)+y=2
4+y=2
subtract 4
y=-2
x=1
y=-2
(1,-2)
solution is
(x,y)
so
add the equations together to cancel y''s
4x+y=2
x-y=3 +
5x+0y=5
5x=5
divide 5
x=1
subsitute
4x+y=2
4(1)+y=2
4+y=2
subtract 4
y=-2
x=1
y=-2
(1,-2)
4x+y=2
x-y=3
Solve 4x+y=2 for y
Add -4x to both sides
4x+y+-4x=2+-4x
y=-4x+2
Substitute -4x+2 for y in x-y=3
x-y=3
x-(-4x+2)=3
Simplify both sides of the equation
5x-2=3
Add 2 to both sides
5x-2+2=3+2
5x=5
Divide both sides by 5
5x/5=5/5
x=1
Substitute 1 for x in y= -4x+2
y=-4x+2
y=(-4)(1)+2
Simplify both sides of equation
y=-2
Answer : y=-2 and x=1
I hope that's help again !